2020
DOI: 10.1002/admi.202000552
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening of Titanium by Equal Channel Angular Pressing ‐ Impact on Oxide Layer Properties of Pure Titanium and Ti6Al4V

Abstract: Equal channel angular pressing (ECAP) as a method applicable to large samples for strengthening metallic materials via severe plastic deformation has recently attracted considerable interest. For biomedical applications, ECAP‐treated pure titanium is a promising alternative for implants subjected to high mechanical loads as it contains no potentially cytotoxic alloying elements. The consequences of an ECAP treatment for the physico‐chemical properties of the air formed passive layers of pure or alloyed titaniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…It has been stated that physicochemical properties of the surface get altered when a material is subjected to various, complex plastic deformations. 30 Titania layer formed on the HE-manufactured Ti has shown to be slightly thicker and covered with a greater amount of hydroxyl groups when compared to the unprocessed substrates. 2 In addition, hydrostatically extruded titanium demonstrates anisotropy of corrosion resistance in synthetic saliva.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been stated that physicochemical properties of the surface get altered when a material is subjected to various, complex plastic deformations. 30 Titania layer formed on the HE-manufactured Ti has shown to be slightly thicker and covered with a greater amount of hydroxyl groups when compared to the unprocessed substrates. 2 In addition, hydrostatically extruded titanium demonstrates anisotropy of corrosion resistance in synthetic saliva.…”
Section: Discussionmentioning
confidence: 97%
“…Apart from wettability and roughness, surface chemistry could also have a vital role in governing the biological properties of a material. It has been stated that physicochemical properties of the surface get altered when a material is subjected to various, complex plastic deformations . Titania layer formed on the HE-manufactured Ti has shown to be slightly thicker and covered with a greater amount of hydroxyl groups when compared to the unprocessed substrates .…”
Section: Discussionmentioning
confidence: 99%
“…Reducing the grain size can improve their mechanical properties and deformability, showing great application potential in the preparation of medical devices and medical materials [3]. Furthermore, a number of studies have shown that titanium and its alloys with ultrafine grains have superior strength, plasticity, fatigue resistance, corrosion resistance, and many other excellent properties, which have been widely used in the fields of aerospace, biomedicine and chemical machinery [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%